Studi Pertumbuhan Rumput Laut Jenis Kotoni (Eucheuma cottonii) dengan Menggunakan Metode Kurung Dasar dan Lepas Dasar di Perairan Geger, Bali - Andreas Pratama Togatorop; I Gusti Ngurah Putra Dirgayusa; Ni Luh Putu Ria Puspitha (Fakultas Kelautan dan Perikanan Universitas Udayana, 2017)
One of the factors that define the success of seaweed is the planting methods It self. It is important because the method will directly affect the seaweed production. The main problem faced by seaweed farmer is declining the production over years. There are several reasons causing that problem, including, predator, desease and environment degradation. The purpose of this research is investigating the effectiveness of two different seaweed planting methods with the respect to the seaweed growth rate. The two methods that mentioned previously are off bottom and off bottom bracket method. The two methods are basically simillar, the first method (off bottom) is a conventional method, on the other hand, the second method was given an additional nets in order to cover the off bottom construction. The space between each seaweed planting on two different methods are defined similar, which are 25 cm. The initial planting weight was measured 100 grams. Observation was done for 42 days (6 week) and data collection was performed every 7 days on total of 10 individual seaweed each treatment. Absolute weight, daily growth rate, daily growth and specific growth rate are calculated. The data analysis will be done using F test at ? = 0.05 (SPSS 12.0). The result found that the growth rate of seaweed (Eucheuma cottoni) under off bottom bracket was not significantly different compared to the off bottom method (?= 0.476).